Numerical Investigation on the Influences of Processing Conditions on Damage in the CFRTP Cutting Using a Novel Elastic–plastic Damage Model - Wang, Fuji; Jin, Xinghai; Wang, Xiaonan; Jia, Zhenyuan; Zhang, Boyu (Applied composite materials, 2022)
The high quality machining of carbon fibre reinforced thermoplastics (CFRTPs) is still a considerable challenge. It is a hot research topic to discuss the influence of machining parameters on the force and damage of CFRTP workpiece by simulation method with low cost. However, in the three-dimensional (3D) cutting process of CFRTP, the dynamic elastic–plastic deformation process of the material under complex loads and the failure of different modes are involved, therefore, it is difficult to accurately simulate the cutting process including the formation of chips and damage. To solve this problem, this paper proposes a new CFRTP elastic–plastic damage model by combining the CFRTP 3D elastic–plastic model and failure criteria (consists of Hashin’s criteria, Puck’s criteria and the failure criteria based on strain energy density) that take into account multiple damage modes. Based on the proposed novel material constitutive model, a finite element (FE) model of the 3D orthogonal cutting of CFRTP is established. The material removal process, chip morphology and cutting force under four typical fibre orientations are predicted, and the results show that 0° fibre orientation produces C-shaped long chips, and 45° fibre orientation produces curled long chips. For the 90° and 135° fibre orientation, the chips are fragmented, and the damage is more serious. The simulation results agree well with the experimental results in terms of chip shape and cutting force, which verifies the validity of the model. Then, the effects of fibre orientation, tool rake angle, tool edge radius and cutting depth on subsurface damage and cutting force are investigated. The subsurface damage depth and cutting force maintain roughly the same trend as the machining parameters change, so reducing the cutting force helps reduce machining damage. The results of this study are helpful for designing tool structures and optimizing process parameters, which are of great significance for suppressing damage in CFRTP machining.